Enforcing Stateful Authorization and Information Flow Policies in Fine - Swamy, Nikhil; Chen, Juan; Chugh, Ravi (Springer Verlag, 2010)
Proving software free of security bugs is hard. Programming language support to ensure that programs correctly enforce their security policies would help, but, to date, no language has the ability to verify the enforcement of the kinds of policies used in practice—dynamic, stateful policies which address a broad range of concerns including forms of access control and information flow tracking. This paper presents Fine, a new source-level security-typed language that, through the use of a simple module system and dependent, refinement, and affine types, checks the enforcement of dynamic security policies applied to real software. Fine is proven sound. A prototype implementation of the compiler and several example programs are available.
ESOP 2010: 19th European Symposium on Programming